2016
DOI: 10.1186/s13075-016-0943-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of fibromyalgia in disease activity and treatment effect in spondyloarthritis

Abstract: BackgroundFibromyalgia (FM) can coexist with Spondyloarthritis (SpA) leading to diagnostic and treatment dilemmas, especially in the presence of enthesitis. With this study we aimed to estimate the prevalence of FM in SpA and to compare the clinical/disease features and TNF inhibitors (TNFi) in patients with/without FM.MethodFM was defined by a score = > 5/6 of the Fibromyalgia Rapid Screening Tool (FiRST). SpA patients (according to the rheumatologist) and consecutively consulting in the day care hospital but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
50
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 29 publications
6
50
1
4
Order By: Relevance
“…This should not be mis interpreted. This may in part explain the higher frequency of enthesitis in SpA patient with associated fibromyalgia [11].…”
Section: Overlap Of Criteria or Interference With Classification?mentioning
confidence: 97%
See 4 more Smart Citations
“…This should not be mis interpreted. This may in part explain the higher frequency of enthesitis in SpA patient with associated fibromyalgia [11].…”
Section: Overlap Of Criteria or Interference With Classification?mentioning
confidence: 97%
“…No fibromyalgia patient fulfilled ASAS classification criteria, but 14 and 34 % of axial SpA patients (without difference between nonradiographic axial SpA and ankylosing spondylitis) fulfilled 1990 and 2010 fibromyalgia criteria, respectively (and 30 and 46 % of RA patients). In the study of Bello [11], no difference in the prevalence of fibromyalgia was found between the patients fulfilling the clinical arm and those fulfilling the imaging arm of the ASAS criteria. In these studies, fibromyalgia presentation did not seem to interfere with classification, even if, in nonrx-axSpA, female gender is more prevalent, as in fibromyalgia.…”
Section: Overlap Of Criteria or Interference With Classification?mentioning
confidence: 99%
See 3 more Smart Citations